Crystal structure of deglycosylated human IgG4-Fc - Davies, Anna M. (Pergamon Press, 2014)
The Fc region of IgG antibodies, important for effector functions such as antibody-dependent cell-mediated cytotoxicity, antibody-dependent cellular phagocytosis and complement activation, contains an oligosaccharide moiety covalently attached to each C(H)2 domain. The oligosaccharide not only orients the C(H)2 domains but plays an important role in influencing IgG effector function, and engineering the IgG-Fc oligosaccharide moiety is an important aspect in the design of therapeutic monoclonal IgG antibodies. Recently we reported the crystal structure of glycosylated IgG4-Fc, revealing structural features that could explain the anti-inflammatory biological properties of IgG4 compared with IgG1. We now report the crystal structure of enzymatically deglycosylated IgG4-Fc, derived from human serum, at 2.7 Å resolution. Intermolecular C(H)2-C(H)2 domain interactions partially bury the C(H)2 domain surface that would otherwise be exposed by the absence of oligosaccharide, and two Fc molecules are interlocked in a symmetric, open conformation. The conformation of the C(H)2 domain DE loop, to which oligosaccharide is attached, is altered in the absence of carbohydrate. Furthermore, the C(H)2 domain FG loop, important for Fcγ receptor and C1q binding, adopts two different conformations. One loop conformation is unique to IgG4 and would disrupt binding, consistent with IgG4's anti-inflammatory properties. The second is similar to the conserved conformation found in IgG1, suggesting that in contrast to IgG1, the IgG4 C(H)2 FG loop is dynamic. Finally, crystal packing reveals a hexameric arrangement of IgG4-Fc molecules, providing further clues about the interaction between C1q and IgG.